Incident Of Defamation On The Internet In United State, United Kingdom And Malaysia - Arul Samy, Charles Arul (2006)
In this research paper the author will analyse and discuss the challenges and issues related to Defamation on the Internet. The focus will be on Internet Defamation in the United States, the United Kingdom and Malaysia.